Antioxidant Evaluation of Facial Toner Formulations Containing Ethyl Acetate Fraction from Garcinia Mangostana L. Fruit using ABTS 2,2'-Azinobis 3-ethyl benzothiazoline 6-sulphonic Acid Method - Sriyanty Sadsyam; Nielma Auliah; Wa Ode Wisna Anto Uko; Nasrawati Basir; Andi Ulfiana Utari (The Indonesian Institute of Science and Technology Research, 2023)
The mangosteen fruit is rich in polyphenols, particularly xanthones, which have potent antioxidant effects. Given the various effects of facial toners and the growing demand for natural skincare products, mangosteen rind may serve as an alternative ingredient in facial toner formulations. This laboratory experimental study aimed to assess the antioxidant activity of facial toner preparations containing the ethyl acetate fraction of mangosteen rind (Garcinia mangostana L.) using the ABTS method at different concentrations (0.2%, 0.4%, and 0.6%). Four facial toner formulas were formulated, with Formula 1 being the control formula without any active substance and Formulas 2-4 containing the ethyl acetate fraction of mangosteen rind at different concentrations. The prepared formulas underwent physical and chemical stability tests, including organoleptic, homogeneity, pH, viscosity, and humidity tests, before and after six cycles of cycling. The antioxidant activity of the formulas was also evaluated using the ABTS method. The results showed no significant difference (p>0.05) in the organoleptic, viscosity, pH, and humidity tests before and after cycling. Formula 3 showed significant (p<0.05) antioxidant activity compared to the other formulas. Therefore, it can be concluded that the ethyl acetate fraction of mangosteen rind (Garcinia mangostana L.) can be formulated into a facial toner with potent antioxidant activity.